Remote ischemic preconditioning delays fatigue development during handgrip exercise - Barbosa, T. C.; Machado, A. C.; Braz, I. D.; Fernandes, I. A.; Vianna, L. C.; Nobrega, A.- C. L.; Silva, B. M. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Ischemic preconditioning (IPC) of one or two limbs improves performance of exercise that recruits the same limb(s). However, it is unclear whether IPC application to another limb than that in exercise is also effective and which mechanisms are involved. We investigated the effect of remote IPC (RIPC) on muscle fatigue, time to task failure, forearm hemodynamics, and deoxygenation during handgrip exercise. Thirteen men underwent RIPC in the lower limbs or a control intervention (CON), in random order, and then performed a constant load rhythmic handgrip protocol until task failure. Rates of contraction and relaxation (Delta Force/Delta Time) were used as indices of fatigue. Brachial artery blood flow and conductance, besides forearm microvascular deoxygenation, were assessed during exercise. RIPC attenuated the slowing of contraction and relaxation throughout exercise (P < 0.05 vs CON) and increased time to task failure by 11.2% (95% confidence interval: 0.7-21.7%, P < 0.05 vs CON). There was no significant difference in blood flow, conductance, and deoxygenation between conditions throughout exercise (P > 0.05). In conclusion, RIPC applied to the lower limbs delayed the development of fatigue during handgrip exercise, prolonged time to task failure, but was not accompanied by changes in forearm hemodynamics and deoxygenation